Organising a collaborative online hackathon for cutting‐edge climate research. (5th April 2022) - Thomas, James; Stone, Emma J.; Mitchell, Dann M.; Seviour, William; Barnes, Clair; Bloomfield, Hannah; Crook, Julia; Jones, Hayley; MacLeod, Calum
Abstract : The 2021 Met Office Climate Data Challenge hackathon series provided a valuable opportunity to learn best practice from the experience of running online hackathons uniquely characterised by the challenges faced by climate data science in the wake of the COVID‐19 pandemic. In particular, the University of Bristol CMIP6 Data Hackathon with over 100 participants from the United Kingdom highlights the advantages of participating in such events as well as lessons learned. A suggested methodology to structure, plan, promote and ensure longevity of the hackathon outputs is described ensuring smoother running of future events.